Why is the 3-kg LPG Cylinder Scarce? A Systematic Literature Review on Supply Chain Disruptions in Indonesia - Sri Yusriani; Shine Pintor Siolemba Patiro (Dinasti International Journal of Education Management And Social Science, 2025)
The scarcity of subsidized 3-kg LPG cylinders in Indonesia has become a critical issue, leading to significant economic and social consequences. This study systematically reviews existing literature to identify the key causes of the shortage, including supply chain disruptions, policy adjustments, distribution inefficiencies, and speculative market behavior. By analyzing journal articles, government reports, and news sources, this paper provides an in-depth understanding of the factors affecting LPG availability. The findings indicate that improvements in supply chain management, better regulatory frameworks, and enhanced monitoring mechanisms are necessary to prevent recurrent shortages.